I am a strange loop - Hofstadter, Douglas R. 1945- (Basic Books, 2007)
Hofstadter's long-awaited return to the themes of Godel, Escher, Bach--an original and controversial view of the nature of consciousness and identity. What do we mean when we say I? Can a self, a soul, a consciousness, an I arise out of mere matter? If it cannot, then how can you or I be here? This book argues that the key to understanding selves and consciousness is a special kind of abstract feedback loop inhabiting our brains. Deep down, a human brain is a chaotic soup of particles, on a higher level it is a jungle of neurons, and on a yet higher level it is a network of abstractions that we call symbols. The most central and complex symbol in your brain or mine is the one we both call I But how can such a mysterious abstraction be real--or is our I merely a convenient fiction?--From publisher.